Dynamic evolution of multidimensional quality characteristics in Lactobacillus-fermented Polygonatum sibiricum Red. and Crataegus pinnatifida Bunge Jiaosu - Yan-Li Ma; Yin-Zhuang Wang; Hai-Yan Yang; Ding-Ding Duan; Yan-Ping Shi; Jun Wang (CyTA - Journal of Food)
This study innovatively investigated the dynamic evolution of multidimensional quality characteristics during lactic acid bacteria co-fermentation of two medicinal-food homologous resources: Polygonatum sibiricum Red. and Crataegus pinnatifida Bunge. Interactions between microbial metabolism and bioactive components throughout fermentation were systematically tracked. Key findings demonstrated that fermentation significantly altered physicochemical properties, organic acid profiles, and functional enzyme activities. Soluble solids decreased to 10.19 °Brix; reducing sugars stabilized at 14.13 g/L and total acidity increased to 11.59 g/L. Lactic and acetic acids rose significantly, while citric and succinic decreased. Protease and amylase activities increased; superoxide dismutase (SOD) peaked then declined. Dominant phenolics shifted from chlorogenic/caffeic acids to chlorogenic acid/rutin. Total polysaccharides and γ-aminobutyric acid (GABA) exhibited fluctuating increases, with GABA remaining elevated. Post-fermentation aromas favored acids, alcohols, and esters, enhancing flavor. These findings provide a novel strategy for precision fermentation of dual-plant Jiaosu with optimized functional and sensory properties.